OPTIMALISASI MEDIA SOSIAL UNTUK MENINGKATKAN TRAFFIC DAN CUSTOMER AWARENESS UMKM DIMASA PANDEMI - ROSA WANDIRA; FANNY HENDRO ARYO PUTRO (KRIDA CENDEKIA, 2022)
The use of social media is growing very fast. Ranging from small children to the elderly use social media for daily use. With the number of social media users, the dissemination of information is getting faster. Many people make the wrong use of social media wisely. But there are still people who do not know how to use social media properly. One of them is business promotion by using the media. Smart use of social media will be very beneficial for it’s users. Therefore, the public needs to be informed about the good and useful use of social media. The success of business’s communication is largely determined by how the business builds an active communication. Communication in a business becomes the foundation of an UMKM in moving and developing towards the desired UMKM goals. The development of adult technology includes yhe use of social media which changes the pattern pf company interaction with the public. One of the audiences targeted by UMUM is the media